ChemInform Abstract: An Expedient Approach to Synthesize Aryl‐α‐ketoamides from Acetophenones and N, N‐Dimethylformamide. Issue 30 (July 2016) - Liu, Weibing; Xu, Songsen; Chen, Cui; Zhu, Zhibo
Abstract: The effective oxidative conversion of acetophenones with DMF, serving as dimethylamine surrogate and solvent, furnishes aryl‐α‐ketoamides in presence of copper oxide and iodine.